Electron injection and acceleration in a twisted laser driven by the light fan - Xiang Tang; Juexuan Hao; Yin Shi (High Power Laser Science and Engineering)
The longitudinal fields of a tightly focused Laguerre–Gaussian (LG) laser can be used to accelerate electron pulse trains when it is reflected from a solid plasma. However, the normal transverse mode of laser beams in high-power laser systems is approximately Gaussian. A routine and reliable way to obtain high-intensity LG lasers in experiments remains a major challenge. One approach involves utilizing a solid plasma with a ‘light fan’ structure to reflect the Gaussian laser and obtain a relativistic intense LG laser. In this work, we propose a way to combine the mode transformation of a relativistic laser and the process of electron injection and acceleration. It demonstrates that by integrating a nanowire structure at the center of the ‘light fan’, electrons can be efficiently injected and accelerated during the twisted laser generation process. Using three-dimensional particle-in-cell simulations, it is shown that a circularly polarized Gaussian beam with